STRENGTHENING METHODOLOGICAL PREPARATION OF PRE-SERVICE FOREIGN LANGUAGE TEACHERS THROUGH INNOVATIVE TECHNOLOGIES: EVIDENCE FROM SELECTED MASTER’S PROGRAMS IN UZBEKISTAN - Erkulova Feruza Melikuziyevna (Research Focus International Scientific Journal, 2026)
In the context of globalization and rapid digitalization, foreign language teacher education requires technology-enhanced methodological preparation that integrates theory, practice, collaboration, and reflective assessment. This study investigates how innovative educational technologies can improve pre-service foreign language teachers’ methodological readiness within MA programs in Uzbekistan. The research was implemented across five institutions—Uzbekistan State World Languages University, Namangan State Institute of Foreign Languages, Samarkand State Institute of Foreign Languages, Denov Institute of Entrepreneurship and Pedagogy, and Kokand State University—selected for their diverse regional and institutional contexts. A hybrid-didactic, modular model was introduced, combining interactive resources, virtual collaboration tools, and indicator-based monitoring with formative assessment. Findings suggest that technology-integrated instruction strengthens methodological competence, reflective practice, professional communication, and adaptive teaching decision-making. The paper concludes with practical implications for scaling technology-supported methodological training in teacher education.